2018
DOI: 10.1002/adma.201706526
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Coordination of Eu–Iminodiacetate to Control Fluorochromic Response of Polymer Hydrogels to Multistimuli

Abstract: New fluorochromic materials that reversibly change their emission properties in response to their environment are of interest for the development of sensors and light-emitting materials. A new design of Eu-containing polymer hydrogels showing fast self-healing and tunable fluorochromic properties in response to five different stimuli, including pH, temperature, metal ions, sonication, and force, is reported. The polymer hydrogels are fabricated using Eu-iminodiacetate (IDA) coordination in a hydrophilic poly(N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
173
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(177 citation statements)
references
References 69 publications
3
173
1
Order By: Relevance
“…For example, Eu complexes can pick up trace amount of water from organic solvents, which has been widely studied for water detection on the basis of the fluorescence quenching . By incorporating red‐emissive Eu 3+ ions in the polymer matrix, others and our group have shown that the responsiveness of polymers can modulate the fluorescent emission of Eu 3+ ions 4b,9a,12. In the current contribution, the dynamic coordination of Eu‐iminodiacetate (IDA) as a key component is used to build up the physical cross‐linking network in the polymer film consisting of interpenetrating polymer network (IPN) ( Figure a).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Eu complexes can pick up trace amount of water from organic solvents, which has been widely studied for water detection on the basis of the fluorescence quenching . By incorporating red‐emissive Eu 3+ ions in the polymer matrix, others and our group have shown that the responsiveness of polymers can modulate the fluorescent emission of Eu 3+ ions 4b,9a,12. In the current contribution, the dynamic coordination of Eu‐iminodiacetate (IDA) as a key component is used to build up the physical cross‐linking network in the polymer film consisting of interpenetrating polymer network (IPN) ( Figure a).…”
Section: Introductionmentioning
confidence: 99%
“…The change in the storage modulus ( G ′) and the loss modulus ( G″ ) was recorded by the strain amplitude test (γ, 1–1000%). The step strain test was performed for three cycles at 1 HZ, which was converted from small strain (γ = 1%, 100 s for each interval) to large strain (γ = 900%, 100 s for each interval) . All photographic images come from the camera (Canon EOS 600D).…”
Section: Methodsmentioning
confidence: 99%
“…A superhydrophobic and mechanically durable biomimicking material was created by combining characteristics of the lotus leaf, mussel, and sandcastle worm . Multifunctional materials with mechanical sensing and self‐healing under magnetic fields and multistimuli were reported. The development of multifunctional materials that integrate mechanochromic and self‐healing properties is highly demanded.…”
Section: Figurementioning
confidence: 99%